Rhizoplane Bacteria and Plant Species Co-determine Phosphorus-Mediated Microbial Legacy Effect - Lang, Ming; Bei, Shuikuan; Li, Xia; Kuyper, Thomas W.; Zhang, Junling (Frontiers in Microbiology, 2019)
Much effort has been directed towards increasing the availability of soil residual phosphorus (P). However, little information is available for the P fertilization-induced biotic P legacy and its mediation of plant P uptake. We collected microbial inocula from a monoculture maize field site with a 10-year P-fertilization history. A greenhouse experiment was conducted to investigate whether bacterial communities, as a result of different P-fertilization history (nil P, 33 and/or 131 kg P kg ha-1 yr-1), affected the growth of a conspecific (maize) or heterospecific (clover) plant, at two levels of current P application (5 and 30 mg P kg-1 soil; P5 and P30). Deep amplicon sequencing (16S rRNA) was used to determine the maize and clover root-associated bacterial microbiome in different rhizocompartments (rhizoplane, rhizosphere, bulk soil). For both maize and clover, rhizocompartment and host identity were the dominant factors shaping bacterial assemblages, followed by P supply level and the inoculum effect was smallest. Bacterial OTU numbers decreased from bulk soil to rhizoplane, whilst specific OTUs were enriched from bulk soil to rhizoplane. A clear hierarchical habitat filtering of bacterial communities was observed in the rhizoplane of the two plant species. The functional prediction of dominant bacterial taxa in the rhizoplane differed between clover and maize, and clover microbiota were more closely associated with P metabolism and maize with carbon cycling. More connected and complex were observed in the clover rhizoplane compared to maize. The microbial legacy effect caused by long-term P fertilization is overridden by host identity and rhizocompartment. Our results highlight the importance of crop diversification in improving P efficiency. The fine-tuning of rhizosphere microbiome in host metabolism indicates that the functions of microbial communities should be integrated into P management to increase P use efficiency and sustainable food production.